PERANCANGAN SISTEM LIBRARY BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Susi Katarina Sianturi; Ade Hendriani (JURSIMA, 2021)
Libraries are part of educational facilities in supporting access to information and knowledge for students and also for the general public. The variety of data processed by the library and the smarter students are in choosing and using library services makes the school have to think of the right solution. At this time data processing in the library of SMA Negeri Carenang Serang still using a manual system, which causes less effective services. The purpose of this study is to implement a web based information system for borrowing and returning library books to make it easier for students to find information on books they want to read and borrow, and to help and facilitate the work of officers in making data reports on books borrowed and books that have been returned, where the system this library information is made by utilizing information technology, namely the internet. The method used in developing this software uses the waterfall model, which is a systematic development model consisting of stages of system requirements analysis, planning, analysis and design and implementation. Data collection methods used to collect the necessary data is observation, interviews and literature study, while the programming language uses PHP and MySQL database. With this system, it is expected to be able to overcome various user needs in obtaining information and make it easier for officers to process library data, produce more accurate reports without errors and can be well documented, effective and efficient in time optimization. Keywords : Design, Information Systems, Library, PHP, MySQL Databases, Website